An Investigation on the Economic Analysis of Wind Turbines - ONAT, Cem; CANBAZOĞLU, Suat (Energy exploration & exploitation, 2007)
Wind energy, one of the renewable energy sources, has now become a global power generation industry competing with other sources of energy generation. While the interest and investments for wind energy recycling systems are gradually increasing worldwide, both the scientific studies and commercial activities in this field in Turkey are expanding everyday. In this study, some economic subjects related with the energy obtained by wind turbines have examined and the effects of blade number and attack angle on annual maximum energy production obtained from the wind turbines having 4415 NACA and LS-1 blade profiles, which are planned to erect in Malatya city, Turkey, have analyzed.